Building a scale to activate belonging to youth and sports forums for some Iraqi provinces from the viewpoint of their staff - عمر سالم غائب ا.د وليد خالد همام (physical education and sport sciences college for women/ Baghdad University, 2021)
The importance of the research lies in activating youth belonging in youth and sports forums, identifying the obstacles facing youth belonging and its manifestations from the point of view of its owners, finding ways to address it, setting the most important requirements, programs and requirements to be provided in re-attracting young people to forums and instilling values, ethics and teamwork, and exploiting their energies and ideas.  In a positive way, investing their spare time, refining their talents, developing their various interests, and deepening the ties between them, in a way that enhances their national belonging and deepens their spirit of giving The current research included building a measure of activating youth belonging, which the researcher will prepare and build according to the conditions and scientific steps, where the research community consisted of (288) affiliates, while the research sample consisted of (204) affiliates that represented the sample of construction and application  The researcher concluded the necessity of re-activating the affiliation in youth forums by providing material factors, feeling the spirit of the group within the forum, and the participation of the members in making some decisions